Impact of Initial Phase of COVID-19 Pandemic on Operations of Stevedore Companies in Seaports: A Case Study of Poland and Ukraine - Michal PLUCINSKI; Ludmila FILINA-DAWIDOWICZ; Marta MANKOWSKA; Iryna SAVELIEVA; Volodymyr SHEMAYEV (Communications of International Proceedings, 2020)
The COVID-19 pandemic has significantly affected the transport industry functioning. Changes in the volume of transported cargo were observed in particular transport modes, and above all in ports transshipments. The aim of the article is to investigate the impact of the COVID-19 pandemic on the selected stevedore companies functioning in seaports during the initial stage of the pandemic. Selected companies operating in Polish and Ukrainian seaports were analyzed as a case study. The condition of chosen transshipment terminals was examined during the first four months from announcement of pandemic in these countries. Survey method was used to conduct the research. On the basis of the prepared questionnaire, the survey was conducted among representatives of cargo transshipment terminals and the impact of the pandemic on the functioning of stevedore companies was examined. It was found that all companies had to introduce changes to the organization of terminal’s operation. However, the impact on the volume of cargo transshipments, ships service and cargo handling was varied. The article presents preliminary research results that will be continued in the future.
Keywords: COVID-19; seaport; stevedore company; cargo handling.